ChemInform Abstract: One‐Pot Sequential Propargylation/Cycloisomerization: A Facile [4 + 2]‐Benzannulation Approach to Carbazoles. Issue 28 (June 2016) - Raji Reddy, Chada; Rani Valleti, Reddi; Dilipkumar, Uredi
Abstract: A novel one‐pot [4 + 2]‐benzannulation approach to substituted carbazoles is accomplished by acid‐catalyzed C3‐propargylation of 2‐alkenyl/aryl indoles with 1‐aryl propargylic alcohols, followed by cycloisomerization.